Developing an evidence base to inform retirement home policy development using an equity and diversity lens: a mixed methods study protocol - Kehoe MacLeod, K.; Wicks, V.; Isenberg, S.R.; Backman, C.; Beogo, I.; Cénat, J.M.; Fisher, S.; Johnston, S.; Kendall, CE.; Manis, D. R.; Muray, M.; Norris, M.; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Retirement homes are an essential support for many older adults as they age. However, retirement homes may not be an option for all, particularly adults with low socioeconomic status or those from linguistic or visible minority groups, in jurisdictions where there are high out-of-pocket costs and limited availability of language- and culturally-concordant home options. Research examining health inequities in facility-based care for older adults has largely focused on the long-term care sector leaving a gap in knowledge and understanding about the care experiences and health outcomes of retirement home residents. The overall aim of this project is to build an evidence base and provide policy recommendations to improve equity in the retirement home sector in Ontario, Canada. Methods We will conduct a multi-phase sequential mixed methods study involving both quantitative and qualitative data. Phase 1 will involve consulting on social and systemic barriers to equity in RHs with our Community Advisory Committee members and advocacy group collaborators. In phase 2, we will lead retrospective cohort studies using Ontario health administrative data to describe and evaluate differences in rates of RH vs. LTC use and differences in healthcare outcomes. In Phase 3, we will conduct semi-structured interviews with older adults and their family partners preparing to enter or having already entered, facility-based care within the prior 6 months to investigate how individuals’ social identity, including language and income, and pragmatic considerations shape decision-making regarding the transition to facility-based care, including choices between retirement homes and long-term care. Findings from Phases 1,2 and 3 will be contextualized in Phase 4 with decision-maker knowledge users, such as from the Retirement Home Regulatory Authority and Ontario Ministries of Health, Long-term Care, and Seniors and Accessibility. Discussion This project will leverage the existing momentum for long-term care reform where evidence of health inequities is well documented, to engage in research in a neighbouring sector that serves older adults with increasingly similar health profiles and complexities. We will disseminate contextualized policy options to both provincial-level decision-makers and community knowledge user partners to help inform future work on equity in retirement homes at different levels of governance.